Interpreting the Will of the People - A Positive Analysis of Ordinal Preference Aggregation - Sandro Ambuehl; B. Douglas Bernheim (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate how individuals think groups should aggregate members' ordinal preferences -that is, how they interpret "the will of the people." In an experiment, we elicit revealed attitudes toward ordinal preference aggregation and classify subjects according to the rules they apparently deploy. Majoritarianism is rare. Instead, people employ rules that place greater weight on compromise options. The classification's fit is excellent, and clustering analysis reveals that it does not omit important rules. We ask whether rules are stable across domains, whether people impute cardinal utility from ordinal ranks, and whether attitudes toward aggregation differ across countries with divergent traditions.
Keywords: C91; D71; 330; preference aggregation; experiment; social welfare analysis